KEWARGANEGARAAN DAN PEMBERDAYAAN EKONOMI, PILAR KESEJAHTERAAN BANGSA - Nikma, Fifi Lailatun; Hilmiyatusoliha, Hilmiyatusoliha; Humaidi, Humaidi (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Citizenship and economic empowerment are the two main pillars that play a role in creating the welfare of the nation. Citizenship not only encompasses the rights and obligations of individuals in participating in the life of the country, but also involves active contributions to social, economic, and political development. A high sense of social responsibility and an understanding of basic rights as citizens are important foundations for creating an inclusive and empowered society. On the other hand, economic empowerment focuses on strengthening the economic capacity of individuals and communities to create economic independence and equitable distribution of welfare. This empowerment can be realized through increasing access to education, skills training, financing, and technological innovations that can open up business opportunities and improve the quality of life. In the Indonesian context, effective economic empowerment must also include equitable development between regions, considering disparities economy that still occurs between urban and rural areas. This study aims to examine the relationship between citizenship and economic empowerment in improving the welfare of the nation. Through a holistic approach that integrates these two aspects, it is hoped that a system will be created that supports inclusive economic growth, reduces social inequality, and creates more equitable opportunities for all Indonesian people. Active citizenship and sustainable economic empowerment are critical foundations in achieving the goals of a just and prosperous nation's welfare. Kewarganegaraan dan pemberdayaan ekonomi adalah dua pilar utama yang berperan penting dalam menciptakan kesejahteraan bangsa. Kewarganegaraan tidak hanya mencakup hak dan kewajiban individu dalam berpartisipasi dalam kehidupan negara, tetapi juga melibatkan kontribusi aktif dalam pembangunan sosial, ekonomi, dan politik. Rasa tanggung jawab sosial yang tinggi dan pemahaman akan hak-hak dasar sebagai warga negara menjadi landasan penting untuk menciptakan masyarakat yang inklusif dan berdaya. Di sisi lain, pemberdayaan ekonomi berfokus pada penguatan kapasitas ekonomi individu dan komunitas untuk menciptakan kemandirian ekonomi dan pemerataan kesejahteraan. Pemberdayaan ini dapat diwujudkan melalui peningkatan akses terhadap pendidikan, pelatihan keterampilan, pembiayaan, dan inovasi teknologi yang dapat membuka peluang usaha serta memperbaiki kualitas hidup. Dalam konteks Indonesia, pemberdayaan ekonomi yang efektif juga harus mencakup pemerataan pembangunan antar wilayah, mengingat disparitas ekonomi yang masih terjadi antara daerah perkotaan dan pedesaan. Penelitian ini bertujuan untuk mengkaji hubungan antara kewarganegaraan dan pemberdayaan ekonomi dalam meningkatkan kesejahteraan bangsa. Melalui pendekatan holistik yang mengintegrasikan kedua aspek tersebut, diharapkan tercipta sebuah sistem yang mendukung pertumbuhan ekonomi yang inklusif, mengurangi ketimpangan sosial, dan menciptakan kesempatan yang lebih merata bagi seluruh rakyat Indonesia. Kewarganegaraan yang aktif dan pemberdayaan ekonomi yang berkelanjutan merupakan fondasi yang sangat penting dalam mencapai tujuan kesejahteraan bangsa yang adil dan makmur.